Ultrastructure and optics of the prism‐like petal epidermal cells of Eschscholzia californica (California poppy) - Wilts, Bodo D. (New Phytol, 2018)
The petals of Eschscholzia californica (California poppy) are robust, pliable and typically coloured intensely orange or yellow owing to the presence of carotenoid pigments; they are also highly reflective at certain angles, producing a silky effect. To understand the mechanisms behind colour enhancement and reflectivity in California poppy, which represents a model species among early‐divergent eudicots, we explored the development, ultrastructure, pigment composition and optical properties of the petals using light microscopy and electron microscopy combined with both spectrophotometry and goniometry. The elongated petal epidermal cells each possess a densely thickened prism‐like ridge that is composed primarily of cell wall. The surface ridges strongly focus incident light onto the pigments, which are located in plastids at the cell base. Our results indicate that this highly unusual, deeply ridged surface structure not only enhances the deep colour response in this desert species, but also results in strongly angle‐dependent ‘silky’ reflectivity that is anisotropic and mostly directional.